Respostas

2014-05-06T11:10:26-03:00
x² + (x + 1)² = 25
x² + (x + 1) . (x + 1) = 25
x² + x² + x + x + 1 = 25
2x² + 2x + 1 - 25 = 0
2x² + 2x - 24 = 0

a = 2;          b = 2;          c = - 24

Δ = b² - 4ac
Δ = 2² - 4 * 2 * (- 24)
Δ = 4 + 192
Δ = 196

x = - b ± √Δ 
      -------------
           2a
x = - 2 ± √196
      ----------------
          2 * 2
x = - 2 ± 14
     --------------
           4
x' = (- 2 + 14) 
÷ 4
x' = 12 ÷ 4
x' = 3

x'' = (- 2 - 14) ÷ 4
x'' = - 16 ÷ 4
x'' = - 4

Resposta: (3; - 4)